PROPAGANDA POLITIK PARTAI GERINDRA DALAM GAME MAS GARUDA PADA PEMILU 2014 (Analisis Deskriptif Game Online Mas Garuda) - Angga Satrya Putra; Surokim Surokim (Jurusan Ilmu Komunikasi UTM, 2015)
The purpose of this study was to determine how the meaning of the look and content of the online game “Garuda Mas”. This game contains aspects of politically charged designations so that it can become a propaganda technique. The subject of this study is the game “Garuda Mas” which has been input on social media Facebook.Methods of data collection using documentary and literature. Data analysis using descriptive techniques. Data validity checking techniques using triangulation source.The results showed that the game “MAS GARUDA” can form the perspective of the players against Mas Garuda as a superhero figure hopes the Indonesian people who are able to overcome all the problems that exist in Indonesia. This game is a form of creative campaigns using propaganda techniques inserted in the game that has the power to change the mindset of every player. Change of mindset occurs because the player did not have an opportunity to think critically on aspects marking contained in the game. By indirectly the players will feel the emotional of this game and assume characterizations “Garuda Mas” in this game is a truth that can be believed.Keywords: Descriptive, Online Games, Mas Garuda, Partai Gerindra